The Bull Theatre, Bishopsgate Street and John Welles: A Creative Nexus for Marlowe, Shakespeare and the Inspiration for The Massacre at Paris? - Geoffrey Marsh (Journal of Marlowe Studies, 2025)
This paper examines the ‘topographical backdrop’ to the creation of The Massacre at Paris and potential intersections between Marlowe and Shakespeare c. 1589/93. The overall purpose is to question how Marlowe and Shakespeare might have been influenced by conversations with neighbours, acquaintances and fellow writers. This social interaction has been termed ‘chat’, a reference to the practical process but also its ephemeral nature. This study is, therefore, also partly about a John Welles, one of the many, mostly long forgotten, officials who kept the wheels of the Elizabethan state turning – one of those usually ‘who are perished as though they had never been born’. Except, unusually with Welles, it is possible to rescue this intriguing character from obscurity to reveal a Londoner, who for over a decade lived a few hundred yards from Marlowe and Shakespeare. That is, when he was not riding the roads of France.